2007
DOI: 10.2139/ssrn.1012699
|View full text |Cite
|
Sign up to set email alerts
|

The Balanced Scorecard as a Knowledge Management Tool: A French Experience in a Semi-Public Insurance Company

Abstract: In this paper we present the Balanced Scorecard, a Strategic Control tool, which is quite famous all around the world and in the European countries. Its principle objective is to articulate planning decisions with control ones thanks to non-financial indicators. The Strategic Control and the Agency Theories constitute the foundation of this tool. But in Northern Europe, some specific Balanced Scorecard have been designed in the framework of the Knowledge Management Theory. To work, the Balanced Scorecard needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The BSC is primarily used for measuring performance, communicating both strategic goals and ways to achieve them [65], [71]. The BSC is a cooperative tool with a focus on development, communication, goal setting, and feedback, helping in strategic decisions by linking the goals to the organizational strategy, making the BSC a relevant management tool for companies to use to achieve their set goals [75]. BSC might be seen as a "vehicle" that helps companies in making breakthroughs [76], as it provides focused and useful information to managers [77].…”
Section: The Impact Of Balanced Scorecard In Systematic Monitoring Ofmentioning
confidence: 99%
“…The BSC is primarily used for measuring performance, communicating both strategic goals and ways to achieve them [65], [71]. The BSC is a cooperative tool with a focus on development, communication, goal setting, and feedback, helping in strategic decisions by linking the goals to the organizational strategy, making the BSC a relevant management tool for companies to use to achieve their set goals [75]. BSC might be seen as a "vehicle" that helps companies in making breakthroughs [76], as it provides focused and useful information to managers [77].…”
Section: The Impact Of Balanced Scorecard In Systematic Monitoring Ofmentioning
confidence: 99%
“…These methods can be classified into four groups (financial measures, intellectual capital, tangible and intangible benefits, and balanced scorecard), but the BSC is considered to be more useful than intellectual capital or tangible and intangible approaches because it provides a comprehensive view of the organisation's actual performance. In a similar context, Wegmann (2008) indicated that the BSC approach is compatible with KM. It is the best approach to evaluate KM within any organisation (Hongmei and Yujun, 2010).…”
Section: Literature Reviewmentioning
confidence: 94%
“…In this regard, the BSC approach is one of different well‐known ways for evaluating the KM and innovation performance by examining the gap between a target and an actual performance of the organisation (Bose and Thomas, 2007; Gonzalez‐Padron et al , 2010; Wegmann, 2008; Yu and Liying, 2009). According to Lee and Lee (2007), several assessment methods are included in the KM performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anthony and Govindarajan (2003) BSC is a very relevant management tool to achieve the company's objectives. Wegmann (2008) BSC can be viewed as a vehicle within organizations, improving its development. Atkinson (2006) BSC is one of the tools that provides focused and useful information to managers.…”
Section: Kerssens-van Drongelen Nixon Andmentioning
confidence: 99%